Administration of Vitamin D Metabolites Affects RNA Expression of Xenobiotic Metabolising Enzymes and Function of ABC Transporters in Rats - Karoline Klumpp; Frauke Lange; Alexandra S. Muscher-Banse; Nadine Schnepel; Kathrin Hansen; Adrian L. Lifschitz; Laura Mate; Mirja R. Wilkens (Journal of Chemistry)
From studies on different species and in cell culture systems, it has been suggested that vitamin D metabolites might affect the metabolism and elimination of xenobiotics. Although most studies performed on rodents and cell cultures report an upregulation of respective enzymes and transporters, data from the literature are inconsistent. Especially results obtained with sheep differ from these observations. As vitamin D metabolites are widely used as feed additives or therapeutics in livestock animals, we aimed to assess whether these differences indicate species-specific responses or occurred due to the very high dosages used in the rodent studies. Therefore, we applied treatment protocols to rats that had been used previously in sheep or cattle. Forty-eight female rats were divided into three treatment and corresponding placebo groups: (1) a single intraperitoneal injection of 1,25-(OH)2D3 or placebo 12 h before sacrifice; (2) daily supplementation with 25-OHD3 by oral gavage or placebo for 10 days; and (3) a single intramuscular injection of vitamin D3 10 days before sacrifice. In contrast to a previous study using sheep, treatment of rats with 1,25-dihydroxyvitamin D3 did not result in an upregulation of cytochrome P450 3A isoenzymes (CYP3A), but a decrease was found in hepatic and intestinal expressions. In addition, a downregulation of P-glycoprotein (P-gp) and breast cancer resistance protein was found in the brain. Taken together, the stimulating effects of vitamin D metabolites on the expression of genes involved in the metabolism and elimination of xenobiotics reported previously for rodents and sheep could not be reproduced. In contrast, we even observed a negative impact on the expression of CYP3A enzymes and their most important regulator, the pregnane X receptor. Most interestingly, we could demonstrate an effect of treatment with 25-hydroxyvitamin D3 and vitamin D3 on the functional activity of ileal P-glycoprotein (P-gp) using the Ussing chamber technique.